Would Anti-Hypertensive Treatment be a Risk Factor for National Health Budget of Turkey in 2023? - Mehmet Bilgehan Pektas; Mustafa Aldemir; Ayhan Pektas; Onder Akci; Ismet Dogan (Medicine Science, 2015)
This study aims to predict the prevalence of hypertension and the cost of anti-hypertensive treatment in future by analyzing the adults diagnosed with hypertension and the drugs prescribed for their treatment in Turkey during a period of five years. This study reviews data related to the patients diagnosed with hypertension amongst the individuals registered within the Medula database of the Turkish Social Insurance Institution from 2009 to 2013. A significant and gradual increase was specified in the prevalence of hypertension during the study period. The number of female patients was significantly higher than the number of male patients over the passing years. The number of anti-hypertensive drug boxes consumed was significantly increased during the study period. Surprisingly, the number of anti-hypertensive boxes annually consumed by the hypertensive patients remained statistically similar between 2009 and 2013. A significant increase was noted in the prescription of angiotensin II receptor blockers, beta blockers, and angiotensin converting enzyme inhibitors during the study period. The cost of anti-hypertensive treatment was found to decrease by 36.7% during the study period. The economical measures currently adopted for drug pricing are successful but health policies developed for the prevention of hypertension are inadequate. [Med-Science 2015; 4(4.000): 2813-24]